Religious Education for Students with Autism According to Their Families and DKAB Teachers - Karasu, Teceli; Yıldız, İbrahim (My University, 2023)
While human beings have common physical attributes and emotions, their diverse experiences, perspectives, and personalities make them beautifully unique and distinct from one another. One of the special groups in which the difference is seen to be significant is autistic people. Their experiences differ from societal norms, and they exhibit variances not only in comparison to ordinary individuals but also within their own community. This situation necessitates making some special arrangements in education. A considerable amount of scientific work has been conducted on how to provide education for students with autism. However, it is difficult to say that the desired level has been reached at the point of religious education, which constitutes an important area of education. Religious education can play a crucial role in the entire development of students with autism, impacting not only their personal growth but also contributing to the formation of a healthy social structure and progress. For this reason, the effects of religious education on students with autism require further exploration through scientific studies. These studies can shed light on the specific benefits and challenges that religious education presents for individuals with autism. By examining the impact of religious education on cognitive, emotional, and social development in students with autism, researchers can identify strategies that promote inclusivity, engagement, and meaningful learning experiences. This knowledge can help educators, parents, and policymakers, to make informed decisions about the implementation of religious education programs for students with autism. Moreover, scientific studies provide an opportunity to develop evidence-based interventions and support systems that address the specific requirements and potential barriers faced by autistic students in religious educational settings. This study aims to determine the religious education needs of students with autism and how these needs can be met. In the study, which was prepared in a qualitative design, data were collected through the interview technique. Since those who know best the religious education needs of students with autism and the ways to satisfy these needs are their families and teachers who work in their education, their opinions were sought. The research study group consists of 6 parents and 5 teachers with different characteristics. While the data of the study was generally analyzed by descriptive analysis method, sometimes content analysis was also applied. As a result of the study, it has been seen that it is essential to determine the appropriate teaching objectives for the students, to use methods and techniques, to prepare teaching materials, and to carry out assessment and evaluation by considering their characteristics and developments. In other words, religious education course teachers need to individualize teaching in a way that can meet the educational needs of students. In this sense, taking measures to make religious education teachers competent can be suggested.
Keywords: Religious Education; Autism; Families; DKAB Teachers; DKAB program